Two new species of Syllidae (Annelida) from Misaki Bay and Sugashima Island, Japan - Springer, Chris; Sato, Daisuke S.; Oguchi, Kohei; Jimi, Naoto; Miura, Toru; Aguado, M. Teresa (Zootaxa, 2025)
The shorelines of Japan host diverse ecosystems, particularly in the shallow coastal waters, which are rich in syllid species. This study describes two new Syllidae species: Virchowia christophi sp. nov., discovered at Misaki and Sugashima Island, and Paraopisthosyllis rufa sp. nov., found at Misaki. Additionally, we provide a redescription of Syllis okadai Fauvel, 1913, based on specimens collected from Misaki. Virchowia christophi sp. nov. shows a unique combination of characters, such as branched nuchal epaulettes together with a complex colouration pattern featuring white, beige, and brown transverse lines, along with white refringent dots, and chaetae with long distal teeth. The second new species, Paraopisthosyllis rufa sp. nov., is distinguished from similar species by its vivid red colouration and segments secondarily triannulated. Paraopisthosyllis rufa sp. nov. is able to generate a secondary ventral tail while the developing stolon (reproductive unit) is still attached to the parental stock. This trait has previously been observed in species of Megasyllis San Martín et al. 2008 and Alcyonosyllis Glasby & Watson, 2001, two genera that are phylogenetically closely related to Paraopisthosyllis Hartmann-Schröder, 1991. This is the first report of the genus Paraopisthosyllis from Japan. Dense ciliation around eyes is identified as a new characteristic of Syllis okadai and its stolons are described in detail. The phylogenetic position of all three species is investigated using maximum likelihood, combining three genes (18S, 16S, COI). Paraopisthosyllis rufa sp. nov. forms a monophyletic clade with other Paraopisthosyllis species. Syllis okadai from Misaki is sister to the already investigated Syllis okadai from Manazuru, Japan. Virchowia christophi sp. nov. has an ambiguous phylogenetic position within Autolytinae since current molecular data suggests that Virchowia Langerhans, 1879 might be paraphyletic.